EVALUATION OF HEPATOPROTECTIVE ACTIVITY OF THE AERIAL PARTS OF PHYLLANTHUS RETICULATES AGAINST PARACETAMOL INDUCED HEPATIC DAMAGE IN RATS - Dash, Swagatika; Pattanaik, Sovan; Rout, Sudhanshu Sekhar; Bose, Anindya (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: The present study deals with evaluation of hepatoprotective effect against paracetamol induced hepatitis in rats and in-vitro antioxidant activity of aerial parts of ethanolic extract (70%) of Phyllanthus reticulates. Methods: Alteration in the levels of biochemical markers of hepatic damage like AST, ALT, ALP and total Bilirubin were tested in both treated and untreated groups. Results: Treatment with ethanolic extract of Phyllanthus reticulates (400 mg/kg) has brought back the altered levels of biochemical markers to the near normal level which is comparable with the standard drug Silymarin. Conclusion: Further the in-vitro antioxidant activity and total phenolic content showed significant result which in turn encourages further evaluation of this plant in future. Keywords: Phyllanthus, Hepatitis, Biochemical markers, Antioxidant activity, Total phenolic content.